Anemia en mujeres gestantes atendidas en el Hospital Básico de Macará durante el año 2019 - Illescas Peralta, Alexander Gabriel (2023)
Anemia is a condition caused by nutritional deficiency that often affects pregnant women in developing countries. Gestational anemia is a public health problem that increases maternal-fetal morbidity and mortality, and the adolescent population is the most affected. This alteration occurs when there is a decrease in the hemoglobin concentration and a reduction in the hematocrit value. This retrospective and quantitative cross-sectional study was carried out to determine the prevalence of anemia in pregnant women which were attended at the Basic Hospital of Macará in 2019. The method of indirect observation of medical records of patients who met the inclusion criteria was used. Of the 279 pregnant women analyzed, 12% had anemia, with 79% mild anemia, 18% moderate anemia, and 3% severe anemia. No association was found between anemia and the age of the pregnant women (p = 0,565). The prevalence of anemia in the studied population was less than 12%, with mild anemia being the most frequent type. In addition, maternal age did not influence the presence of anemia in this population